Model Strategi Pemasaran Benih Ikan Nila Dengan Variabel Mediasi Kepuasan Konsumen Pada Pokdakan Ulam Merta Asih Bangli-Bali - Wiratni, Ni Kadek Nunung Ari; Panggabean, Donwil; Ridhowati, Sherly (Universitas Batangahari Jambi, 2026)
his study aims to analyze the effect of seed quality and market share on marketing strategy, with customer satisfaction as a mediating variable in Nile tilapia hatchery enterprises. This research employs a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected through questionnaires distributed to Nile tilapia hatchery business actors and subsequently analyzed using measurement and structural models. The results indicate that all constructs meet the criteria of validity and reliability. Path analysis results show that seed quality and market share have a positive and significant effect on customer satisfaction and also significantly influence marketing strategy. Furthermore, customer satisfaction is proven to have the most dominant effect on marketing strategy. The indirect effect test results demonstrate that customer satisfaction significantly mediates the relationship between seed quality and market share on marketing strategy. These findings indicate that the success of marketing strategies is not solely determined by product quality and market coverage but is highly dependent on the level of customer satisfaction. This study reinforces the concept of customer value-based marketing and provides practical implications for fisheries business managers of Pokdakan Ulam Merta Asih in enhancing competitiveness and business sustainability through improvements in product quality and customer satisfaction